Múltiples estrategias metodológicas: Materializando un concepto sociológico para investigaciones en educación contable - Lopes, Iago França (2024)
This research aims to answer the following question-problem: How can the use of multiple methodological strategies be applied to create a research instrument that concretizes Bauman’s “liquid modernity” conception, decoding and explaining socio-academic experiences of stricto sensu accounting postgraduate students (in the strict sense)? Therefore, the objective of the research is to explain a method to create a research instrument that implements sociologist Bauman’s conception on Liquid Modernity, intending to decode socio-academic experiences of stricto sensu postgraduate accounting students (in the strict sense). In terms of theory, the research covers Liquid Modernity concepts and interprets the discussions proposed by Bauman (2001) so as to understand the socio-academic spaces related to experiences. With regards to concretization of Bauman’s ideas, live broadcasting, focus groups, observation and pre-tests were used as methodological strategies in order to create and validate a research instrument based on Bauman’s perspective. The results evidenced the permeability of quantitative and qualitative elements for the materialization of the sociological concept in the accounting field. Hence, it could be suggested that, within Bauman’s conception of liquid modernity, socio-academic experiences of students enrolled in accounting postgraduate programs (PPG) are immersed in experiences that are influenced by interpersonal and demographic aspects which are related to educational and professional environments.